The farmer and progress - Darnell, Harry A. (My University, 1892)
Introduction: It used to be said if a man had brains he could make a doctor, a lawyer, or a minister; if active and skillful with tools, he would do for a mechanic; if good-looking and talkative, must be a society man or merchant. If he had none of these, or in fact no other commendable qualities or accomplishments he would do for a farmer. There were yet in the very recent past a large number of people who advocated similar ideas. Even at the present time, it is not an uncommon thing to hear the young man or woman advised to prepare for a more respectable, rememerative and easy occupation. This, it seems to me is one of the principal reasons why farming has not ranked with the trades or professions. There are none so sure to fail as those who abuse themselves, for the man who “kicks” himself is likely to have the assistance of his neighbors.
Citation: Darnell, Harry A. The farmer and progress. Senior thesis, Kansas State Agricultural College, 1892.
Morse Department of Special Collections
Keywords: Career; Farmer; Agriculture; Occupation; Theses; Manuscripts (documents)